Effect of laser parameters on colour marking of Ti6Al4V titanium alloy - Syakila, A. R.; Jamaludin, M. N.; Quazi, M. M.; Aiman, Mohd Halil; Arslan, A. (IOP Publishing, 2024)
Colour laser marking is a contemporary method for adding colours onto metal surfaces, suitable for creating logos, barcodes, metal crafts, and jewelry. This study focused on colour laser marking on the biomedical alloy Ti6Al4V (TC4), examining how different colours manifest on its surface. Power settings ranged from 9 W to 18 W, while frequencies spanned 500 kHz to 2000 kHz. The research investigated how altering laser frequency and defocus distance influenced colour variation. Surface features were assessed using 3D optical microscopy, revealing texture and roughness traits. Results illustrated a spectrum of colours, shifting from the alloy's original silver hue to shades like blue, gold, orange, shiny silver, violet, and several greys. Each colour displayed distinct surface texture and roughness parameters. The highest mean roughness of 2.504 μm occurred with grey, while silver had the lowest at 0.504 μm. Nevertheless, trends differed when measuring parameters like maximum peak-to-valley height and valley depth, emphasizing surface topography's role in colour effects. This research advances the understanding of colour laser marking's intricacies on TC4 alloy, providing insights into optimizing laser settings for specific colour outcomes and underlining the nuanced relationship between colour, texture, and surface characteristics.